Analysis of Heavy Metal Distribution in Regional Sediments Batang Ayumi River Flow - Fatma Suryani Harahap; Adi Syaputra (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
The presence of heavy metals in waters can be sourced from mining, household, agricultural waste and industrial wastes. Some heavy metals are toxic such as Cu, Hg, and Pb can accumulate in aquatic sediments. Sediments that are contaminated with heavy metals will endanger the organisms that live in them. This research aims to identify the concentrations of heavy metals Cu, Hg, and Pb in sediments in the Batang Ayumi River. This research uses a descriptive exploratory method by conducting a survey in advance. Determination of sampling locations using purposive sampling method at four determined stations. This research uses an Atomic Absorption Spectrophotometer. Data analysis was performed by comparing the test result data with the quality standards issued by the IADC / CEDA. The test results show that the concentration of Cu, Hg and Pb in the sediment has a value smaller than the target level value, so the substance in the sediment is not too dangerous for the environment.